Pomoc publiczna dla przedsiębiorców ze środków Państwowego Funduszu Rehabilitacji Osób Niepełnosprawnych w celu przeciwdziałania bezrobociu - Koza, Andrzej (Public assistance for entrepreneurs from the means of state rehabilitation fund for the disabled in relation to unemployment prevention, 2005)
For over 13 years State Rehabilitation Fund for the Disabled has been the main financial instrument assisting state activities for the prevention of unemployment among the disabled. Financial means transferred to entrepreneurs from this Fund for the means of professional rehabilitation are perceived as public assistance and as such are subject to the rigors of provisions on public assistance for entrepreneurs with all due consequences. In the years 2000-2003 the Fund provided entrepreneurs with the assistance of about 3 billion zł in total.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1091, s. 33-40